2018
DOI: 10.1155/2018/1057242
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Greenhouse Gas Emissions from Different Land-Use Systems: A Case Study of CO2 in the Southern Zone of Ghana

Abstract: The emission of greenhouse gases (GHGs) results in global warming and climate change. The extent to which developing countries contribute to GHG emissions is not well known. This study reports findings on the effects of different land-use systems on GHG emissions (CO2 in this case) from two locations in the southern zone of Ghana, West Africa. Site one (located at Kpong) contained a heavy clay soil while site two (located at Legon) contained a light-textured sandy soil. Land-use systems include cattle kraals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…In this case, it is logical to indicate that when afforestation and reforestation practices are coupled with various climate change adaptation activities, they significantly enhance sinks of greenhouse gases and management of C in the terrestrial biosphere. In line with this, the findings of the study conducted by MacCarthy et al (2018) reveal that covering the area with trees would play a large role in C capture and sequestration. From this, one can understand that if this practice is widely employed and protected in a sustainable way, it could reverse the current situations of land-use patterns and reduce the impacts of climate change in the long run, thereby increasing C sequestration.…”
Section: Implication Of Lulc Dynamics To Greenhouse Gasessupporting
confidence: 63%
“…In this case, it is logical to indicate that when afforestation and reforestation practices are coupled with various climate change adaptation activities, they significantly enhance sinks of greenhouse gases and management of C in the terrestrial biosphere. In line with this, the findings of the study conducted by MacCarthy et al (2018) reveal that covering the area with trees would play a large role in C capture and sequestration. From this, one can understand that if this practice is widely employed and protected in a sustainable way, it could reverse the current situations of land-use patterns and reduce the impacts of climate change in the long run, thereby increasing C sequestration.…”
Section: Implication Of Lulc Dynamics To Greenhouse Gasessupporting
confidence: 63%
“…Carbon sequestration potential of an ecosystem is a function of climate, land management practices, land-use patterns, soil types and soil characteristics, and topographic heterogeneity [4][5][6][7][8][9][10]. Some studies concurred that any ecosystem site could either be a carbon sink (negative flux) or a carbon source (positive flux) depending on the weather patterns [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric Carbon-dioxide (CO2)is one of the greenhouse gasesand it is known for its heat absorption and sunlight warming. In addition to this, CO2 in particular dissolves into the ocean thereby producing carbon acid and lowering the ocean's pHvalue [1]. It has been reported that higher concentration of CO2 increases the growth of cereal crops but reduces the nutritional value of key staple crops [2].…”
Section: Introductionmentioning
confidence: 99%
“…Its occurrence has been traced to some socio-economic characteristics, income, car ownership [2], poor rail accessibility and urban density [3], human activity and natural system [4]. The impact has been projected to be greater in the southern Asia and African region [1,5] and may likely result to inability to keep global average temperature increase below 2 o c [6]. With these in view, it suffices to consider the fundamental processes that are believed to generate the subject matter and then build a detailed model that can be used for control and also make predictions.…”
Section: Introductionmentioning
confidence: 99%